Prevention or delay of type 2 diabetes by pharmacological or lifestyle interventions - Emini Sadiku, Merita (Array, 2008)
Summary: The purpose of this essay is to review available evidence on lifestyle, pharmacological and herbal remedies influence on the prevention or delay of the onset of type 2 diabetes and adapting these lessons from clinical trials to clinical practice. A Medline literature search from 1997-2006 was performed to identify articles on the prevention or delay of type 2 diabetes in adults. The limits were practical guidelines, systematic reviews, randomized controlled trials (meta-analyses), as full text articles or abstracts, and with no limits for the period searched.Different trials and systematic reviews have revealed that pharmacological and lifestyle interventions can reduce the rate of progression to type 2 diabetes in people with impaired glucose tolerance.The overall goal for diabetes prevention is to reach and maintain an active, healthy weight with a tendency toward a hypo-caloric diet. Pharmacological interventions also reduced diabetes risk. However, lifestyle changes were more effective and are recommended as first-line strategy. For pharmacological interventions adverse effects need to be fully understood to enable the potential harms and benefits to be assessed. Therefore, better approach to patients for lifestyle changes should be achieved through a structured program in order to delay or prevent type 2 diabetes. Multidisciplinary healthcare teams may provide more intensive counseling and increase the contact the patient has with the overall healthcare system